Urinary Neutrophil Gelatinase-Associated Lipocalin: A Biochemical Marker for Early Diagnosis of Urinary Tract Infections in Adults: Urinary Neutrophil Gelatinase Associated Lipocalin - Ayub, Hafiz Muhammad Ahsan; Khan, Muhammad Nadim Akbar; Sultana, Saadia; Qayyum, Shazia (Pakistan Journal of Health Sciences, 2024)
Urinary tract infection is an infection of the urinary system. Early diagnosis is helpful in timely treatment. Urinary NGAL is a new method that is used for early diagnosis of UTI. Objective: To evaluate the efficacy of urine neutrophil gelatinase-associated lipocalin (uNGAL) as a biochemical marker for early UTI diagnosis. Methods: A analytical study was conducted from Oct 2022 to Oct 2023, A total of 90 subjects having signs and symptoms of UTI irrespective of age and gender. The study participants were divided into three groups. Patients with UTI were included in diseased group (n=60) and healthy individuals were enrolled as controls in Group-I (n=30). SPSS v-26 was used for data analysis. Descriptive and Inferential statistics were applied. Results: The mean age of the participants was 30.5±6.9 years, 23(26%) were male, and 67(74%) female. These participants were divided into three groups; Group-I (control) had 30(33.3%) participants, group-II (patients with signs and symptoms but negative culture) had 34(37.8%), and group-III (patients with signs and symptoms and positive cultures) had 26(28.9%) participants. No growth was seen in participants of Group-I, II, and Group-III had positive cultures including E. coli (16.7%), S. aureus (10%), Candida Sp. (1.1%) and Klebsiella Pneumonea (1.1%) with significant findings (p<0.001). A significant difference among groups was noticed with uNGAL levels (p<0.001); Group-III had raised uNGAL levels of 361 ± 65.5ng/ml. Conclusion: Urinary NGAL is a promising biomarker that can detect UTIs even in the absence of clinical symptoms, enabling early diagnosis and treatment of UTIs.